Masculinity in Adolescent Males’ Early Romantic and Sexual Heterosexual Relationships - David L. Bell MD, MPH; Joshua G. Rosenberger MPH, PhD; Mary A. Ott MD, MA (American Journal of Men's Health, 2015)
There is a need to understand better the complex interrelationship between the adoption of masculinity during adolescence and the development of early romantic and sexual relationships. The purpose of this study was to describe features of adolescent masculinity and how it is expressed in the contexts of early to middle adolescent males’ romantic and sexual relationships. Thirty-three 14- to 16-year-old males were recruited from an adolescent clinic serving a community with high sexually transmitted infection rates and were asked open-ended questions about their relationships—how they developed, progressed, and ended. Participants described a high degree of relationally oriented beliefs and behaviors related to romantic and sexual relationships, such as a desire for intimacy and trust. The males also described a more limited degree of conventionally masculine beliefs and behaviors. These beliefs and behaviors often coexisted or overlapped. Implications for the clinical care of similar groups of adolescents are described.